2022
DOI: 10.21203/rs.3.rs-1310197/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 variants’-Alpha, Delta, and Omicron D614G and P681R/H mutations impact virus entry, fusion, and infectivity

Abstract: SARS-CoV-2 variants acquire mutations to survive within the host and evade immunity. In addition to harboring D614G mutation in spike domain, P681R/H mutation at the junction of the S1/S2 furin cleavage site, is found to be the key mutation in variants of concerns (VoC); Alpha, Delta, and Omicron (B.1.1.519). The impact of these acquired mutations on entry, transmissibility, and infectivity of SARS-CoV2 VoC is not clearly identified. Here, using the spike-based pseudovirus, Delta and D614G+P681R synthetic muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…(38). VOCs have a better ability to survive and evade host defense mechanisms than the original virus (39). The most striking difference between the Omicron variant and previous variants was that the symptoms of OD were significantly less prevalent during Omicron's prevalence.…”
Section: Target Cells Of Sars-cov-2 In the Nasal Epitheliummentioning
confidence: 95%
“…(38). VOCs have a better ability to survive and evade host defense mechanisms than the original virus (39). The most striking difference between the Omicron variant and previous variants was that the symptoms of OD were significantly less prevalent during Omicron's prevalence.…”
Section: Target Cells Of Sars-cov-2 In the Nasal Epitheliummentioning
confidence: 95%
“…A recent study conducted by Khatri et al (2022) showed that the Delta synthetic mutant exhibited a considerable increase in pseudovirus entry, fusion, and infectivity [252]. A leucine-to-arginine substitution at position 452, which is present in Delta but not in the Omicron variant, is known to boost affinity for ACE2 receptors located on the surface of a variety of human cells, including lung cells [6].…”
Section: Affinity To Angiotensin-converting Enzyme 2 (Ace2) Receptorsmentioning
confidence: 99%
“…According to Khatri et al (2022), in the absence of TMPRSS2, Omicron may enter cells easily via ACE2-dependent endocytosis and is extremely prone to cathepsin L inhibitors, such as E64d [252]. Higher transmissibility is expected if the overlapping Omicron mutations maintain their known effects, especially because of mutations near the furin cleavage site [331].…”
Section: Affinity To Angiotensin-converting Enzyme 2 (Ace2) Receptorsmentioning
confidence: 99%